French Travellers and Adventurers’ Retrospect of Idol Worship, Sanctity of the Ganga and Divinity of Cow - Kundra, Sakul (Animo Repository, 2016)
The 17th and the 18th-century French travellers’ and adventurers’ perceptions about the Hindu socio-religious beliefs, practices, and myths have always been a relatively un-researched but fascinating area. This article, based on a study of their memoirs (both translated and un-translated), purports to analyze their perceptions of and observations on three specific aspects of the Hindu socio-religious world in North India during the Mughal period, namely, idol worship, reverence of cow, and Ganga. Objective of this article is to comprehend French travellers’ vision towards identity formation of idol worship, its sacredness, and the practices attached to promulgate its belief among Hindus in northern India during the period of research. One discerns the unexplored reasons for devotional proliferation of idol worship, their propagators, and means adapted to glorify its principles. Further, the article intents to examine the discourse of dissemination of superstitious practices attached to Hindu doctrine of metempsychosis in regard to cow being revered as a sacred animal. An attempt has been made to scrutinize the sanctified effects of sacred water of river Ganga as well as its relevance in the life of the Hindus. One tried to research the French perspective about reasons given by Hindus to consider Ganga as the most revered river and elucidated by varied myths, illusions, and sagas to consider it as a symbol of purity. Similar rituals practiced at Jagannath temple in Puri are explored in order to analyze them through French travellers’ eyes. Efforts are made to reflect how European Western culture comprehend the Orient’s varied socio-religious beliefs and “superstitious” ideologies in relation to Hinduism practiced in northern India.